100- kyr cyclicity in volcanic ash emplacement: evidence from a 1.1 Myr tephra record from the NW Pacific - Schindlbeck, Julie Christin; Jegen, Marion; Freundt, Armin; Kutterolf, Steffen; Straub, Susanne M.; Mleneck-Vautravers, Maryline J.; McManus, Jerry F. (Scientific reports, 2018)
It is a longstanding observation that the frequency of volcanism periodically changes at times of global climate change. The existence of causal links between volcanism and Earth’s climate remains highly controversial, partly because most related studies only cover one glacial cycle. Longer records are available from marine sediment profiles in which the distribution of tephras records frequency changes of explosive arc volcanism with high resolution and time precision. Here we show that tephras of IODP Hole U1437B (northwest Pacific) record a cyclicity of explosive volcanism within the last 1.1 Myr. A spectral analysis of the dataset yields a statistically significant spectral peak at the ~100 kyr period, which dominates the global climate cycles since the Middle Pleistocene. A time-domain analysis of the entire eruption and δ18O record of benthic foraminifera as climate/sea level proxy shows that volcanism peaks after the glacial maximum and ∼13 ± 2 kyr before the δ18O minimum right at the glacial/interglacial transition. The correlation is especially good for the last 0.7 Myr. For the period 0.7-1.1 Ma, during the Middle Pleistocene Transition (MPT), the correlation is weaker, since the 100 kyr periodicity in the δ18O record diminishes, while the tephra record maintains its strong 100 kyr periodicity.